Implementasi Program Seni Tilawah Dalam Membaguskan Bacaan Al-Qur’an Di Rumah Tahfidz Al-Ghifari Desa Sialang Dusun Iv - Amalia, Ade; Junaidi (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2023)
The implementation of the art of reciting the Koran is the application or implementation of reading the Koran using rhythm or song. The purpose of this research is: to find out the model of the method used in carrying out the recitation art program at the Tahfidz Al-Ghifari House. The data used is qualitative data. Qualitative data obtained from interviews and direct observation. The research results obtained, the model and learning method used is by using the tallaqi method (directly).